(untitled) (Medico Legal Update, 2019)
The need for cybersecurity measures in the field of healthcare is becoming more prescient given both the increased sophistication of cyber criminal activity and the increased prevalence of low-security mobile devices1. Also, hospitals have been slower to increase cybersecurity, but has become an increasing target due to the increased security of the financial industry2. The implementation of the Health Information Portability and Accountability Act (HIPAA) has made patient records more portable and accessible, and created more opportunities for breaches1. The Health Information Technology for Economic and Clinical Health Act (HITECH) promoting greater implementation of electronic systems for coordination and records. The medical field is also becoming increasing dependent on connectivity, and people are wary of the threats to automated and robotic safety procedures. The threat of high dependence on technology for medical practices presents risks in and of itself, such as cases where it disrupts communication between healthcare professionals, or fails to account for user failures that could be prevented with better feedback before implementation. Healthcare providers are in a difficult position, trying to balance the need for quick, responsive systems for users, and need for cybersecurity measures that can slow down the computer system. In the following pages, Lewin’s field mapping approach will facilitate an analysis of the current largest cybersecurity threats and current research on the best methods of thwarting these vulnerabilities.